Estrutura e estabilidade dos politipos dos filossilicatos 1:1 por primeiros princípios - Carlos Esteves Teixeira Júnior (2016)
The geological knowledge about the earth was built by the intense and brilliant work of many minds over the centuries. Despite this, there is a practical limitation of this knowledge because of human inability to directly access interior portions of the planet. This causes that the forms of knowledge about the structure and terrestrial dynamics are indirect and / or inductive. This work sought understand the stability and influence of phyllosilicates 1:1, dioctahedral and trioctahedral, by first principles calculations with imposed geodynamic environment conditions. Traditionally, the first group is represented by the mineralogical triad kaolinite, dickite and nacrita, while the second by the series lizardite, antigorite and chrysotile. Based on the work of Zvyagin, the dioctahedral polytypes were reconstructed following a methodology proposed by the author of this thesis. The trioctahedral polytype used here were based on the work of Bailey. The calculated electronic, mechanical and thermodynamic properties were compared with results of "experimental" phases, obtained from the refinement of real mineral structures described in several studies. The calculations on the theoretical and experimental structures were confined to the square of temperature and pressure conditions of crustal events. Additionally, the thermodynamic path of stability of these structures around the typical geodynamic conditions could be better understood. The crustal environment associated with the dioctahedral series was the deep continental basins while the trioctahedral series tied in the subduction of oceanic plates on continental blocks environment. The imposition of conditions in the temperature and pressure in the calculations of the mechanical and thermodynamic properties allowed constructing a reasonable picture of the conditions of existence and influence of these different theoretical and experimental structures.